Colonial law in Africa, 1946-1966. (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2017)
These gazettes contain copies of the laws and ordinances which were introduced in the years they cover. Each item was originally published as the Government Gazette for a colony and year. Their contents include tenders of property, probate records and insolvency notices. This is the third part of the three part series Colonial Law in Africa. These papers cover the Mau Mau uprising, the creation of the first legislative councils and legal changes to transfer power to those councils. These gazettes were published alongside the African Blue Books of Statistics during the 19th and 20th centuries.
Date range: 1946-1966.
Keywords: Law -- Africa